WOMEN TIKTOKERS’ OFFENSIVE LANGUAGE UTILIZATION DURING THE FREE PALESTINE CAMPAIGN - Issanty, Nadia Mauliana; Ruminda, Ruminda; Assiddiqi, Hasbi (Politeknik Negeri Jakarta, 2024)
Linguists argue women's linguistic politeness is influenced by societal perceptions, but as gender equality advances, the concept of women's language evolves, involving debates on offensive language. Therefore, this study investigated the utilization of offensive language by women TikTokers in the Free Palestine campaign. The research focuses on the study of issue statements regarding the various forms of offensive language used by women TikTokers participating in the Free Palestine campaign. This study employs Battistella's (2005) theory, which posits four distinct categories of offensive language. This study employed a qualitative approach, utilizing data obtained from the transcriptions of three female TikTok users, namely Kayla, Katie, and Heba. According to the research findings, women who use TikTok employ all of Battistella's offensive language categories a total of 223 times in their videos. Among women TikTokers, the term